KETEPATAN KOORDINAT BUJUR LINTANG DAN UTM PADA GOOGLE-EARTH SKALA 1 : 1000 - Ilham Marsudi (Universitas Negeri Yogyakarta, 2010)
ABSTRACTThis paper intends to test and find out the accuracy or the deviation informationlatitude longitude coordinates (λ, φ) or UTM which is informed on the Google-Earthimage. The research is started by conducting registry longitude-latitude coordinatesand UTM at some points in the Google-Earth, then it is overlaid with visual mapcoordinates of the earth scale 1: 25 000 Bakosurtanal publish. Both coordinates areplotted in the ArcView program in the form of theme-point. Subsequently both thesethemes in overlay can be seen visually for deviations from these coordinates anddistance can be measured as well as its deviation from the second point with amagnification of up to show the level of detail scale 1: 1000. Conclusions can bedrawn that the longitude-latitude coordinates or UTM on Google-Earth can not be usedfor technical maps in large scale, but it was enough for making the planning maps inscale 1: 25.000.